The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/mpp.13215
|View full text |Cite
|
Sign up to set email alerts
|

Immune recognition of the secreted serine protease ChpG restricts the host range of Clavibacter michiganensis from eggplant varieties

Abstract: Bacterial wilt and canker caused by Clavibacter michiganensis (Cm) inflict considerable damage in tomato‐growing regions around the world. Cm has a narrow host range and can cause disease in tomato but not in many eggplant varieties. The pathogenicity of Cm is dependent on secreted serine proteases, encoded by the chp/tomA pathogenicity island (PI), and the pCM2 plasmid. Screening combinations of PI deletion mutants and plasmid‐cured strains found that Cm‐mediated hypersensitive response (HR) in the Cm‐resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 66 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…It was revealed that the plasmid genes (including pat-1 , ppaJ , CelA , phpA , and phpB ), plasmid quantity, PAI on the chromosome, and transcription regulatory factors are involved in the pathogenicity of C. michiganensis [ 43 , 44 , 45 ]. ChpG encodes a transmembrane protein that mediates the immune response of multiple eggplant varieties, whereas some virulence factors remain undiscovered and unevaluated [ 25 ]. The high relative expression levels of CelA , xysA , and xysB , which encode cellulase or xylanase, in the △ pbpC mutants indicated that the canker symptom is primarily caused by cell-wall-degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was revealed that the plasmid genes (including pat-1 , ppaJ , CelA , phpA , and phpB ), plasmid quantity, PAI on the chromosome, and transcription regulatory factors are involved in the pathogenicity of C. michiganensis [ 43 , 44 , 45 ]. ChpG encodes a transmembrane protein that mediates the immune response of multiple eggplant varieties, whereas some virulence factors remain undiscovered and unevaluated [ 25 ]. The high relative expression levels of CelA , xysA , and xysB , which encode cellulase or xylanase, in the △ pbpC mutants indicated that the canker symptom is primarily caused by cell-wall-degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The second factor contributing to virulence is pat-1 , which encodes a putative serine protease and has been identified on plasmid pCM2 [ 23 , 24 ]. A number of transcriptional regulators also associated with virulence, such as Vatr1 and Vatr2 , are located in chromosomal regions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the plant‐pathogenic members of Clavibacter , putative genes associated with pathogenicity may carry different roles, which may depend on their plant host. In C. michiganensis , some chp serine proteases are known to not affect virulence when deleted (Peritore‐Galve et al, 2021 ) and some are recognized to restrict pathogen growth and disease in related plant species outside of tomato (Park et al, 2022 ; Verma & Teper, 2022 ). Conversely, in C. capsici , one chp protease ( chpG ) is a putative pathogenicity factor critical for disease as knockouts and natural variants lacking chpG are less virulent (Hwang et al, 2020 ).…”
Section: Pathogenicity Mechanismsmentioning
confidence: 99%
“…Consequently, recognition of pathogen-associated molecular patterns (PAMPs) is thought to play an important role in plant defense to Cn and Cm. Proteases have been shown to elicit a nonhost resistance in the case of Cm and Clavibacter sepedonicus (Cs) ( Nissinen et al 2009 ; Lu et al 2015 ; Verma and Teper 2022 ). Bacterial cold shock proteins, cell wall components, exopolysaccharides, extracellular cell wall degrading enzymes secreted by bacteria, and even degraded fragments from the host cell wall may function as PAMPs to elicit plant defense ( Balaji et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%